Case report: Therapeutic response of front-line cadonilimab plus chemotherapy on patient with advanced lung adenocarcinoma harboring STK11 genetic aberration - Feng, Du; Jiang, Huixin; Chen, Gengjia; Guan, Wenhui; Yi, Lin; Zhu, Yue; Li, Yijia; Huang, Gengda; He, Bin; Tang, Junlong; Tang, Yujie; Zeng, Jiyuan; et al. (Frontiers in Immunology, 2024)
The STK11 gene mutation is a common genetic alteration in non-small cell lung cancer (NSCLC) and is significantly associated with poor responses to current immunotherapy regimens. Despite its prevalence, there is currently no established standard for front-line treatment in this subtype of NSCLC, underscoring the increasing need for personalized therapeutic strategies. In this report, we present a case of a patient with STK11-mutant NSCLC who was treated with first-line cadonilimab (10mg/kg) in combination with pemetrexed (500mg/m^2) plus carboplatin (AUC=5), resulting in a notable extension of progression-free survival (PFS). This case highlights the potential efficacy and feasibility of combining immunotherapy with chemotherapy in patients with STK11-mutant NSCLC. Additionally, we provide a review of recent advancements in research related to STK11 mutations in lung cancer as reported in the literature.